Current Intelligent Injectable Hydrogels for In Situ Articular Cartilage Regeneration. (2nd April 2020) - Liao, Youguo; He, Qiulin; Zhou, Feifei; Zhang, Jingwei; Liang, Renjie; Yao, Xudong; Bunpetch, Varitsara; Li, Jiajin; Zhang, Shufang; Ouyang, Hongwei
Abstract: A high number of sport injuries result in damage to articular cartilage, a tissue type with poor self-healing capacity. Articular cartilage tissue is a sophisticated hydrogel, which contains 80% water and possesses strong mechanical properties. For this reason, synthetic hydrogels are thought to be an optimal material for cartilage regeneration. In the last decade, more than 2, 000 research papers pertaining to "hydrogel and cartilage" have been published. Due to its biomimetic properties and user-friendly nature, especially in the field of minimal invasive surgery, intelligent injectable hydrogel have gradually become a focal point in cartilage research in recent years. In this review, we systematically summarize current "state-of-the-art" manufacture technologies of injectable hydrogels including ion-induced, thermo-induced, non-induced chemical, and light-induced crosslinking. We also review current strategies for designing intelligent injectable hydrogels, such as component-based, mechanical property-based and structure-based intelligent design to simulate the natural articular cartilage. Lastly, the applications of intelligent injectable hydrogels for cartilage regeneration are presented, and their outlooks for future clinical translation is dicussed.